Efisiensi Sistem Rainwater Harvesting (RWH) Bandar Udara Internasional Yogyakarta dalam Memanfaatkan Air Hujan Budaya - Faisya Haqqin Abrari; Prabang Setyono; Muhammad Amin Sunarhadi (Center for Environmental Research, LPPM, Universitas Sebelas Maret, 2026)
Almost all rainwater that falls on the surface will flow into rivers and end up in the sea and is not utilized optimally. This problem requires efforts to utilize rainwater by capturing and collecting rainwater for reuse. The purpose of this study was to determine the quantity, quality, economic feasibility and application of SDGs in the YIA Airport Rainwater Harvesting system. The method used is quantitative and descriptive. The results of this study indicate that the efficiency of rainwater utilization for PDAM for 4 years is IDR 1,871,196,000.00 with a potential volume of rainwater that can be accommodated of 19,704 m3. The quality conditions of rainwater and clean water are in accordance with Permenkes No. 2 of 2023 except for the Total Coliform and E. Coli parameters which exceed the quality standards. The Rainwater Harvesting system is economically feasible but is in the slow category in terms of investment returns. This condition is indicated by the NPV value of IDR 3,063,091,281.00; IRR 25.5%; Net B/C -0.30 and PBP 2,688 days. Rainwater Harvesting YIA Airport has implemented SDGs program points 6 and 12 by utilizing natural resources to reduce conventional water use and ensure sustainable sanitation.